RANCANG BANGUN SISTEM KAMERA PEREKAM PORTABLE MENGGUNAKAN RASPBERRY PI TERINTEGRASI DENGAN SERVER BERBASIS INTERNET OF THINGS - Abdul Rakhman; Suroso; ABI DZAR AL GIFARRY (Jurnal Qua Teknika, 2021)
Camera recorders in general will continue to record continuously without stopping and this will take up storage space. This is deemed less effective because of its limited capacity and also in terms of security, the recorded information is very vulnerable. Therefore, in this study, a portable recording camera system was designed using multi sensors and integrated raspberrypi with the server and then the recording results will automatically be sent to the server and forwarded to the user's email. This portable recording system uses a PIR sensor (Passive Infrared Receiver) HC-SR501, Raspberry Pi 3 B plus, Infrared led light, Pi camera, KY-037 sound sensor, SMTP Server (Simple Mail Transfer Protocol). When the PIR sensor detects movement or the KY-037 sound sensor detects sound, it will be processed by the Raspberry Pi and then the Pi camera will automatically perform the recording process periodically. When finished, the recording results will be sent directly to the user's email via the SMPT (Simple Mail Transfer Protocol) server provided by Google. All processes in this tool system work completely automatically.